SEEKING JUSTICE IN ISLAMIC LEGAL PLURALISM: The Dispute of Child Best Interests in Marriage Dispensation in Indonesia - Rohmawati, Rohmawati (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
The principle of the best interests of children must be the main consideration in adjudicating applications for marriage dispensation. However, its implementation becomes problematic when faced with provisions on the ability to grant marriage dispensations for urgent reasons. This article examines how the best interests of children are implemented in legal applications for marriage dispensation in religious court. It employs a socio-legal approach with a maqāsid al-syarī'ah cum-mubadalah perspective. This article proposes that the principle of the best interests of children is yet considered by judges effectively in deciding the cases. This does not reflect the protection of the child’s life, heredity, intellect, property, and religion, and does not consider the unique experiences of women both biologically and socially. Judges have a biased perspective in measuring the meaning of maturity and readiness of girls to marry, ignoring children's rights in education and reproductive health, and subordinate women in the spiritual realm.